The Comparative Effect of Aerobic Dance and Cycling on The Psychological Well-being of Adolescent Girls - Kurniati, Rizki; Broto, Danang Pujo; Paramitha, Sandey Tantra; Taroreh, Bangkit Seandi; Rasyono, Rasyono; Saleh, R Agung Purwandono (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2025)
This study examines the comparative effects of aerobic dance and cycling on the psychological well-being of adolescent girls in Indonesia, a country where mental health awareness among youth is growing yet remains under-implemented in educational settings. As physical education increasingly seeks cost-effective and accessible methods to promote mental wellness, this research provides valuable insights. Sixty tenth-grade female students aged 15–16 were selected via random sampling and assigned to a 2×2 factorial experimental design. Data were collected using a validated psychological well-being questionnaire and analyzed using two-way ANOVA and Tukey's HSD test at a significance level of 0.05. The results revealed three main findings: (1) aerobic dance significantly outperformed cycling in improving psychological well-being; (2) participants with higher fitness levels exhibited better psychological outcomes than those with lower fitness; and (3) a significant interaction effect was observed between exercise type and fitness level, with the most significant improvement seen in high-fitness participants who engaged in aerobic dance. These findings emphasize the importance of considering both exercise modality and physical fitness level in designing school-based interventions to promote adolescent mental health.